ADVERSE DRUG REACTIONS AMONG PATIENTS IN DEPARTMENT OF MEDICINE IN A TERTIARY CARE TEACHING HOSPITAL, KOLLAM - JS, Beena; Raj MR, Rakesh Praveen; R, Reeja; Nair R, Bindulatha; L Pavithran, Reshma (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Pharmacovigilance practices are still in the infancy in India, more so in South India. adverse drug reactions (ADRs) are often underreported and the risks are higher in adults and elderly due to the association of comorbidities, self-medication, combination of indigenous systems of medicines and modern medicine, and so on. The present study was done with the objective to analyze the ADRs among patients in the general medicine department, Government Medical College, Kollam. The primary objective is to determine the prevalence and nature of ADRs and secondary objective to assess the causality, severity, and preventability of the ADRs. Methods: In this cross-sectional study done in the Department of Medicine, Government Medical College, Kollam, 1000 patients of either sex were analyzed using CDSCO ADR reporting forms and the approved scales for causality, severity, and preventability. Results: Among 1000 patients studied, the prevalence of ADRs was 7.6%. The most common system involved were dermatological (41%) followed by cardiovascular (18%) and gastrointestinal and neurology (16% each). Majority of the ADRs came under probable (48.7%) with a Naranjo score of 5 (40.8%), of moderate severity (65.8%) and not preventable (71.1%). Conclusion: ADRs pose a major problem needing hospital stay or prolonging the duration of stay. Developing an ongoing ADR reporting system with continuous motivation and creating awareness among the healthcare professionals for reporting suspected ADRs will help to continue reporting and improving the patient safety. Improved communication of health-care professionals with the pharmacovigilance centers should be promoted for better patient healthcare.